Resident Training and Treatment for Acute Abdominal Cases in a Secondary Emergency Medical Care Center employing a North American-style ER System - Hagiwara, Eiichirou; Yanaga, Katsuhiko; Matsumoto, Takatugu; Ogawa, Takeki (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2006)
Our hospital's Emergency Department, a designated secondary emergency medical care center, has adopted a North American-style ER operation format, in which one-on-one training is provided by specialist ER physicians in line withthe requirement that all residents undergo training in emergency medicine. Residents are expected to acquire asignificant amount of experience and to master many procedures during their emergency medicine training. Eachresident sees approximately 300 patients during the two-month training period, including many acute abdominal cases.Under the direct supervision of the attending doctor, residents are able to treat patients effectively according to theseverity and acuteness of their condition. They are trained to interpret blood test results, X-ray examinations and otherdiagnostic tests, and are instructed to employ sonography instead of relying on multidimensional images, such as CTscans, from the outset. If emergency surgery is necessary, treatment responsibility is smoothly transferred to therelevant department thanks to a 24-hour backup system that encompasses all clinical departments. The resident whotook charge of the patient in the emergency room is also encouraged to attend the operation whenever possible. In thisway, through close collaboration between the ER and surgical departments, an adequate training system has beendeveloped for the treatment of acute abdominal illnesses at this hospital.